Hubungan Gangguan Mental Emosional dan Obesitas Sentral: Literature Review - Rahmawati, Dwi; Djuwita, Ratna (UI Scholars Hub, 2024)
The prevalence of central obesity, both globally and in Indonesia, continues to increase. Mental and emotional disorders are one of the contributing factors to central obesity. In previous studies, it was known that the relationship between emotional mental disorders and obesity can occur in bidirections, where emotional mental disorders can cause central obesity or vice versa. This literature review aims to find out more about the relationship between emotional mental disorders and central obesity from various countries. The searching for articles used 4 databases (Scopus, Science Direct, Proquest, and Pubmed) with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. The keywords used to search for literature are (Emotional mental disorders) OR (Stress) AND (Central obesity) OR (Abdominal obesity) And (Adults). The analysis was carried out on 6 research articles from America, Finland, China, Iran, Brazil, and Mexico. The research articles used cohort, case-control, and cross-sectional study designs. This literature review resulted in emotional mental disorders associated with central obesity, and were more common in women. This relationship is influenced by other factors, such as age, gender, marital status, education, occupation, smoking status, physical activity, sedentary behavior, alcohol consumption, emotional eating and binge eating. In overcoming central obesity, it is necessary to consider a person's emotional mental condition, especially in women. In addition, further research is needed on other factors that may influence the relationship between emotional mental disorders and central obesity.